2018
DOI: 10.1096/fj.201701118r
|View full text |Cite
|
Sign up to set email alerts
|

Silica‐induced initiation of circular ZC3H4 RNA/ZC3H4 pathway promotes the pulmonary macrophage activation

Abstract: Phagocytosis of silicon dioxide (SiO) into lung cells causes an inflammatory cascade that results in fibroblast proliferation and migration, followed by fibrosis. Circular RNAs (circRNAs) are a subclass of noncoding RNAs that are present within mammalian cells; however, researchers have not determined whether circRNAs are involved in the pathophysiologic process of silicosis. To elucidate the role of these RNAs in SiO-induced inflammation in pulmonary macrophages, we investigated the upstream molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 47 publications
1
75
0
Order By: Relevance
“…Elevated level of macrophages can infiltrate in the inflamed synovium tissue and cause inflammatory lesions and joint damage in RA 3 . Some circRNAs are reported to be specifically expressed in macrophages and affect their differentiation, infiltration, activation, and function in particular tissues [28][29][30] . There are different expression patterns of circRNAs in diverse polarized macrophages primarily including pro-inflammatory M1 and antiinflammatory M2 macrophages 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated level of macrophages can infiltrate in the inflamed synovium tissue and cause inflammatory lesions and joint damage in RA 3 . Some circRNAs are reported to be specifically expressed in macrophages and affect their differentiation, infiltration, activation, and function in particular tissues [28][29][30] . There are different expression patterns of circRNAs in diverse polarized macrophages primarily including pro-inflammatory M1 and antiinflammatory M2 macrophages 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that circRNAs and lncRNAs can participate in post-transcriptional regulation through the competitive binding of miRNAs. 18 Some studies have shown that circRNAs can bind to many miRNAs to participate in normal growth and development. 19 However, only a few bovine circRNAs, such as circSNX29, have been shown to play a key role in growth.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages subtypes (M1-type macrophages and M2-type macrophages) play a key role in the induction and regulation of specific immune responses and the development and recovery of disease. It have been indicated that circZC3H4 take part in SiO 2 induced macrophage activation through HECTD1/ZC3H12A dependent ubiquitin-proteasome pathway (43). Circ-RasGEF1B is necessary for macrophage activation after exposure to lipopolysaccharide (LPS) (44).…”
Section: Circrnas In Immune Regulationmentioning
confidence: 99%